Clostridium difficile infection and immune checkpoint inhibitor–induced colitis in melanoma: 18 cases and a review of the literature. Issue 3 (27th June 2023) - Vuillamy, Chloé; Arnault, Jean-Philippe; Fumery, Mathurin; Mortier, Laurent; Monestier, Sandrine; Mansard, Sandrine; Bens, Guido; Duval-Modeste, Anne-Bénédicte; Funck-Brentano, Elisa; Jeudy, Géraldine; Machet, Laurent; Chaby, Guillaume; et al.
Abstract : Immunotherapy has become the standard of care for several types of cancer, such as melanoma. However, it can induce toxicity, including immune checkpoint inhibitor–induced colitis (CIC). CIC shares several clinical, histological, biological, and therapeutic features with inflammatory bowel disease (IBD). Clostridium difficile infection (CDI) can complicate the evolution of IBD. We aimed to characterize the association between CDI and CIC in patients treated with anti-CTLA-4 and anti-PD-1 for melanoma. Patients from nine centers treated with anti-CTLA-4 and anti-PD-1 for melanoma and presenting with CDI from 2010 to 2021 were included in this retrospective cohort. The primary endpoint was the occurrence of CIC. The secondary endpoints were findings allowing us to characterize CDI. Eighteen patients were included. Eleven were treated with anti-PD-1, four with anti-CTLA-4, and three with anti-PD-1 in combination with anti-CTLA-4. Among the 18 patients, six had isolated CDI and 12 had CIC and CDI. Among these 12 patients, eight had CIC complicated by CDI, three had concurrent CIC and CDI, and one had CDI followed by CIC. CDI was fulminant in three patients. Endoscopic and histological features did not specifically differentiate CDI from CIC. Nine of 11 patients required immunosuppressive therapy when CDI was associated with CIC. In nine cases, immunotherapy was discontinued due to digestive toxicity. CDI can be isolated or can complicate or reveal CIC. CDI in patients treated with immunotherapy shares many characteristics with CDI complicating IBD. Stool tests for Clostridium difficile should be carried out for all patients with diarrhea who are being treated with immunotherapy.